A refined methodology for validation of information models derived from flowsheet data and applied to a genitourinary case. (17th September 2020) - Westra, Bonnie L; Lytle, , Kay S; Whittenburg, Luann; Adams, Mischa; Ali, Samira; Furukawa, Meg; Hartleben, Stephanie; Hook, Mary; Johnson, Steve; Collins Rossetti, Sarah; Settergren, Tess (Theresa)
Abstract: Use of electronic health record data is expanding to support quality improvement and research; however, this requires standardization of the data and validation within and across organizations. Information models (IMs) are created to standardize data elements into a logical organization that includes data elements, definitions, data types, values, and relationships. To be generalizable, these models need to be validated across organizations. The purpose of this case report is to describe a refined methodology for validation of flowsheet IMs and apply the revised process to a genitourinary IM created in one organization. The refined IM process, adding evidence and input from experts, produced a clinically relevant and evidence-based model of genitourinary care. The refined IM process provides a foundation for optimizing electronic health records with comparable nurse sensitive data that can add to common data models for continuity of care and ongoing use for quality improvement and research.